Test platform design for regenerative braking of hub-motor. Issue 1 (31st December 2016) - Han, Chengwei; Qi, Ziming; Qiu, Hao
Abstract: Electric brake experiment of hub-motor is preliminary basis of the regeneration braking control strategy. A regenerative braking test bench of hub-motor is designed in which the test and control system is developed based on Labview and NI virtual instrument. The physical structure, signal acquisition hardware and test system principle of the bench are introduced. The bench can test torque and speed of the hub-motor, on which the electric brake experiment and etc. can be done. Through the unloaded glide and electric brake experiments, the results show that the design of the bench is reasonable and control modes of the test and control system is feasible. Furthermore, the test bench can provide important references for regeneration braking control strategy and motor performance tests.